The allocation of the revenues in federal state (Al-Mansour Journal, 2010)
Every state all over this world can't survive and keep on achieving its projectwithoutkfinancial income.Even the existence of all states rely on bases offinance .various types of government cant keep on with their activities withoutconsidering their financial affairs ,whether in simple state or composite state ,unified ,because the need to revenues is the main point for all forms of thestates.But the important thing we will discuss is how will be the allocation ofincome in federal states, this matter may raise many problems, and issues thatmight rise conflicts, and enter the crossroads that we should choice one ofthem.More over the important of this topic seems as result of the federal shapewhich Iraq adopted. Therefore we must research about this changing becauseit is a new move whether in political or financial field in Iraq to avoid anymistake in application.It is well known to reader what we mean by federalism as form of governancewhere the authorities are constitutionally divided between central governmentand smaller units (provinces, states) .in other words optional union betweenthe states of the federated states, lead to its transformation to a single legal orpolitical system and with the retention of these parts of the united personalprivacy and identity, and there is delegation of the central union of some of thejoint powers authority with the retention of some of these parts or the states .And thus we note that retain include the power of legislative, executive andindependent judiciary within the constitutional sphere, is well known, thepossibility of the adoption of the central government fiscal policy to reduce thecompetence of states in various ways, including the granting of aid, whetherconditional or no, even to financing of projects or to fill the provinces deficit inits treasury, or other needs.د. بان صلاح الصالحي Alsalhi. S Ban. Dr10 2009 الاول تشــرین 25-24 العــاشـر العلمــي المؤتمـــر th Scientific Conference 24-25 Oct.2009In order to avoid the difficulties and problems mast follow the federalconstitution , the foundation upon which all the institution of the state aredepend and built their respective responsibilities , and thus may provide moreexplicit on how the allocation of revenues between the state and federalprovinces .On the other hand, highlights role of the state budget, as is general budget ofthe federal state, which is the method of organization of state revenues andexpenditures, and thus is an essential tool for the organization of the provincesquota of income, contribute the executive and the legislative as representativeof people to developed and approved the state by it.There are many reasons which may be taken into consideration whendetermining the quotas, one of these factors is the contribution of the state infederal state in general, and the possibilities of each state and its ownresources that can be used as private resources, as well as geographic andenvironmental differences, differences in population …Thus, we can in accordance that principles find ways to allocate the federalstate revenues.